Immunochromatographic Strip-Based Detection of Entamoeba histolytica-E. dispar and Giardia lamblia Coproantigen - Pillai, Dylan R. (American Society for Microbiology, 1999)
BIOSITE Triage was 68.3% sensitive and 100% specific for the detection of Entamoeba histolytica-E. dispar (n = 71) compared to Alexon-Trend’s ProSpecT test (reference standard) using fresh-frozen stool. Neither test is able to distinguish E. histolytica from E. dispar. Triage was 83.3% sensitive and 100% specific compared to microscopy (formalin-ether concentrates and permanent stains) for the detection of Giardia lamblia.